Regulation of ofloxacin resistance in Escherichia coli strains causing calf diarrhea by quorum-sensing acyl-homoserine lactone signaling molecules - Wang, Zi; Sun, Miao; Wang, Yongqiang; Shi, Jinchuan; Gao, Wei; Han, Dongxu; Zeng, Fanjun; Sanren; Du, Liyin; Ma, Hongxia; Liu, Kai (Frontiers in Veterinary Science, 2025)
Escherichia coli is a major pathogen responsible for calf diarrhea. However, it has developed resistance to many antimicrobial drugs for their inappropriate usage. The bacterial quorum sensing system transmits information between bacteria, it's important in regulating bacterial virulence, drug and acid resistance and so on. This system can found in Gram-negative bacteria and operates through acyl-homoserine lactone (AHL) signaling molecules. In this study, a type I quorum sensing AHL, N-Octanoyl-L-Homoserine lactone (C8), was added to E. coli growth medium to investigate its regulatory functions in drug resistance. After screening out the strains of E. coli that showed an obvious regulatory effect to the drug ofloxacin (OFX), transcriptomic sequencing was performed on the E. coli strains from the sub-inhibitory concentration group that concentration plus C8 group, and the control group. It shows that C8 significantly influenced resistance to OFX and the minimum inhibitory concentration of OFX in the tested strain was significantly increased. To Analyze transcriptome sequencing results identified 415 differentially expressed genes between the control and sub-inhibitory concentration groups, of which 201 were up-regulated and 214 were down. There were 125 differentially expressed genes between bacteria treated with a sub-inhibitory concentration of OFX and those treated with C8, of which 102 were up-regulated and 23 were down. Finally, It found that to adding the C8 significantly increased the resistance of tested bacteria to OFX. Data from transcriptome sequencing on differently expressed genes helps to explain how the type I quorum sensing system controls drug resistance in E. coli.